Loss of intestinal sympathetic innervation elicits an innate immune driven colitis - Rose A. Willemze; Olaf Welting; Patricia van Hamersveld; Caroline Verseijden; Laurens E. Nijhuis; Francisca W. Hilbers; Sybren L. Meijer; Balthasar A. Heesters; Joost H. A. Folgering; Harold Darwinkel; Philippe Blancou; Margriet J. Vervoordeldonk; et al. (BMC, 2019)
Abstract Background Both the parasympathetic and sympathetic nervous system exert control over innate immune responses. In inflammatory bowel disease, sympathetic innervation in intestinal mucosa is reduced. Our aim was to investigate the role of sympathetic innervation to the intestine on regulation of the innate immune responses. Methods In lipopolysaccharide (LPS)-stimulated macrophages, we evaluated the effect of adrenergic receptor activation on cytokine production and metabolic profile. In vivo, the effect of sympathetic denervation on mucosal innate immune responses using 6-hydroxydopamine (6-OHDA), or using surgical transection of the superior mesenteric nerve (sympathectomy) was tested in Rag1−/− mice that lack T- and B-lymphocytes. Results In murine macrophages, adrenergic β2 receptor activation elicited a dose-dependent reduction of LPS-induced cytokines, reduced LPS-induced glycolysis and increased maximum respiration. Sympathectomy led to a significantly decreased norepinephrine concentration in intestinal tissue. Within 14 days after sympathectomy, mice developed clinical signs of colitis, colon oedema and excess colonic cytokine production. Both 6-OHDA and sympathectomy led to prominent goblet cell depletion and histological damage of colonic mucosa. Conclusions We conclude that the sympathetic nervous system plays a regulatory role in constraining innate immune cell reactivity towards microbial challenges, likely via the adrenergic β2 receptor.